Comparative study of hair grown in virgin coconut oil, coconut oil and brand X hair grower - Olivar, Lalaine U. 4 0 16; 5 (2007)
u
Thesis: (B.S. Biology)-Pamantasan ng Lungsod ng Maynila, 2007.
Keywords: 2 -- 0; 6; 20; 20; 2